Diversity Of Crustacean Isopod In Bangka Island Of North Sulawesi - Manikmayang Annisaqois; Gustaf Mamangkey; Rose O.S.E. Mantiri; Markus T. Lasut; Farnis B. Boneka; Reiny Tumbol; Deiske Sumilat; Wolfgang Wägele (Jurnal Ilmiah PLATAX, 2020)
Information about marine isopods in Indonesian water is scarce. This research aimed to inventory isopods in nearshore habitats of Northern Sulawesi using a morphological approach to identify the species. Sampling was done in several spots in Bangka Island considering three different habitats: coral rubble, mangrove roots, and seagrass beds. These habitats are known to be suitable for isopods to feed, reproduce, and hide from bigger predators. There is 7 group of Isopod found in totals, such as Anthuridea, Asellota, Bopyridae, Cirolanidae, Gnathiidae, Limnoriidea, and Sphaeromatidea. In the family of Anthuridae, there are 2 suspected new species and required further identification.Keywords: Marine Isopod, Ecology, Bangka Island, North Sulawesi.AbstrakInformasi mengenai isopoda laut di perairan Indonesia masih sangat sedikit. Penelitian ini bertujuan untuk menginventarisasi isopoda di habitat dekat pantai Sulawesi Utara menggunakan pendekatan morfologi untuk mengidentifikasi spesies. Pengambilan sampel dilakukan di beberapa titik di Pulau Bangka dengan pertimbangan tiga jenis habitat berbeda: serpihan karang, akar mangrove, dan padang lamun. Habitat tersebut merupakan tempat isopoda mencari makan, bereproduksi, dan bersembunyi dari predator. Dari hasil identifikasi ditemukan 7 kelompok isopoda, yakni Anthuridea, Asellota, Bopyridae, Cirolanidae, Gnathiidae, Limnoriidea, dan Sphaeromatidea. Diduga ada 2 species yang baru di kelompok Anthuridae yang masih perlu penelitian lebih lanjut.Kata kunci: Isopoda Laut, Ekologi, Pulau Bangka, Sulawesi Utara.